2023
DOI: 10.3389/fendo.2023.1120774
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin levels in chronic kidney disease: A systematic review and meta-analysis

Abstract: IntroductionChemerin as an inflammatory biomarker has gained attention in its biomarker capability. Several studies measured its levels in chronic kidney disease (CKD), as one of the common non-communicable causes of mortality and morbidity. Hence, this systematic review and meta-analysis aimed to investigate this association.MethodsPubMed, Scopus, Embase, and the Web of Science databases were systematically searched for studies investigating chemerin levels in any CKD stage (including end-stage renal disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Others have also demonstrated a relationship with renal function in diabetics [41]. We observed a significant relationship between higher chemerin and KDIGO stage in KTRs, which falls in line with pooled observation for the general population [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Others have also demonstrated a relationship with renal function in diabetics [41]. We observed a significant relationship between higher chemerin and KDIGO stage in KTRs, which falls in line with pooled observation for the general population [18].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the 16kDA polypeptide size, increased chemerin may be derived from reduced excretion or increased stimulation of adipokine levels, which is consistent with decline in concentrations after KTx [18,43]. Alternatively, excessive activation of inflammatory, endothelial and oxidative cascades following renal insult may also contribute to higher chemerin levels [18]. In the present study, we observed serum chemerin concentrations showed an increase with higher CKM (numerical) and CKD stage, but also exhibited a prognostic role for dialysis therapy risk.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…OSA independently increases the risk of insulin resistance [32]. Systematic reviews and meta-analyses confirm an association between OSA and insulin resistance determined via an elevated HOMA-IR [33] or the atherogenic index of plasma, calculated according to the formula: log (serum triglyceride level/serum HDL-c level) [34]. Compared to usual care, OSA therapy with continuous positive airway pressure (CPAP) [35][36][37][38][39][40] or implantation of a mandibular advancement device [41], improves insulin resistance without changing BMI, supporting a role for tissue hypoxia in the pathogenesis of insulin resistance.…”
Section: Obstructive Sleep Apnea Is Associated With Insulin Resistancementioning
confidence: 92%